The Impact of Environmental Science Courses on Students’ Concern about Environmental Sustainability - Valmay, Altelah Anisa; Salsabila, Disya Berliani; Salma, Sabrina; Prihantono, Gigih (International Journal of Psychosocial Rehabilitation, 2020)
Environment is an aspect of life that has to be preserved. Nowadays, environmental management tends to be economy-oriented, where humans often carry out exploratory actions to fulfil their interests. Improper environmental management can cause long-term damage which might put all aspects of humans’ life at risk. Humans are the main element of the environment who can greatly influence the continuity of environmental quality. The young generation, especially students, plays an important role in environmental sustainability. Students who are studying at the university are those who will bear great responsibility as a successor to later civilization. Students should be aware of their obligations, rights, and authority over the environment in order to be able to exploit environment’s potential without destroying it, for the sake of humanity’s survival.